Case Report: Acute Renal Infarction in a Child With Coarctation of Aorta - Zhang, Qing-Yun; Tseng, Min-Hua; Ding, Jhao-Jhuang; Huang, Jing-Long (Frontiers in Pediatrics, 2021)
Renal arterial infarction can present with hematuria, proteinuria, and hypertension, features often linked to glomerular disease. An aortic aneurysm is an extraordinarily rare complication of coarctation of the aorta. Acute renal infarction caused by emboli from the aortic aneurysm is a possible complication that has not been reported. We herein report a 10-year-old boy presented with hematuria, proteinuria, hypertension, and skin rashes on both lower extremities mimicking acute glomerulonephritis, but actually resulting from acute renal infarction caused by coarcted aneurysm-associated thrombus. He was successfully treated with surgical excision of coarcted aorta and aneurysm followed by subcutaneous low molecular weight heparin without recurrence.